Eficiencia del control interno y la gestión administrativa de la Municipalidad Distrital de San Pablo en el periodo 2024 - Freitas Pinedo, Mohasir (2025)
This research aimed to explore the relationship between internal control efficiency and administrative management within the Municipality of San Pablo in 2024. A quantitative, correlational design was employed, using Spearman's correlation to assess the strength and significance of the relationship between these two variables. The findings revealed a moderate to strong positive correlation (Rho = 0.6682, p-value = 0.0485), confirming that a more efficient internal control system contributes to enhanced administrative management. Furthermore, the study investigated other dimensions such as the relationship between the control environment and strategic planning, risk assessment, and communication within the organization. While significant correlations were found in certain areas, such as communication and productivity (Rho = 0.6428, p-value = 0.0399), other relationships, such as those between risk evaluation and goal fulfillment, did not show statistical significance. These results suggest that while internal control plays a crucial role in administrative effectiveness, other factors like leadership, resource allocation, and organizational culture must also be considered. This research provides valuable insights for municipal management, emphasizing the need to strengthen internal control systems while integrating communication and strategic planning processes for improved performance and decision-making.